2014
DOI: 10.2514/1.c032054
|View full text |Cite
|
Sign up to set email alerts
|

Fifth Drag Prediction Workshop: Computational Fluid Dynamics Studies Carried Out at ONERA

Abstract: This article presents the computational studies which have been performed at ONERA in the context of the 5 th AIAA Drag Prediction Workshop (DPW-5). A grid convergence process and a buffet onset study have been carried out using a Reynolds-averaged Navier-Stokes (RANS) solver and far-field methods. In this work, the Multi-Block (MB) grids of the Common Research Model (CRM) provided by the DPW-5 Committee are employed and a new meshing strategy involving overset techniques and Cartesian grids is tested. All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…These structured grids have produced consistent results and relatively good agreement with the National Transonic Facility (NTF) experimental data [25]. The different characteristics of these meshes are indicated in Table 1.…”
Section: Reference Grids and Datasupporting
confidence: 55%
See 4 more Smart Citations
“…These structured grids have produced consistent results and relatively good agreement with the National Transonic Facility (NTF) experimental data [25]. The different characteristics of these meshes are indicated in Table 1.…”
Section: Reference Grids and Datasupporting
confidence: 55%
“…3. If the expected accuracy for drag prediction is below the count (1 drag count = 0.0001 CD, where CD is the drag coefficient), the grid convergence study shown in [25] has indicated that the fourth refinement level (L4/17 million elements) is sufficient to evaluate the aerodynamic coefficients correctly.…”
Section: Reference Grids and Datamentioning
confidence: 98%
See 3 more Smart Citations